(untitled) (Architecture Image Studies, 2025)
What started as a dormitory online forum for college students has become a mega power in social media world. This is how social media, a fad among college students or a rage in social networking domain, can be described in a nutshell. Then later it become most powerful tool for education. This study paper researcher studied effectiveness of social media in media educational technology.